ANALYSIS OF PSYCHOANALYSIS THEORY IN ELEMENTARY AGE CHILDREN ANALYSIS: JOURNAL SINTA 2 TO 6 - Khoirunisa; Maemonah; Aditiya, Novela (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
The purpose of this study is to see the analysis of psychoanalytic theory in elementary age children, which consists of three parts of personality, namely the id, ego and super ego. The method used by the researcher is descriptive qualitative in a literature review approach. using the method of using data or related scientific papers using the object of research or collecting data that is library in nature and then identified using relevant library materials. Literature review means the activity of conducting relevant research using theories that can be found in the literature, reports by searching, reading and describing. The data collection technique in this study uses journal articles literature, the web or the internet, or other sources and takes from articles related to the discussion of psychoanalytic theory and optimizes the superego to produce students' character in a better personality. which have been published in the journal Sinta 2-6 as many as 6 scientific articles. Then process and conclude research without going through field research. The results of this study are maximizing the super ego in character education to control the super ego to prevent the id's ability to grow in humans.